Reduced Histone H3 Lysine 9 Methylation Contributes to the Pathogenesis of Latent Autoimmune Diabetes in Adults via Regulation of SUV39H2 and KDM4C - Xi-yu Liu; Hong Li (Journal of Diabetes Research)
Aims. Latent autoimmune diabetes in adults (LADA) is an autoimmune disease of which the mechanism is not clear. Emerging evidence suggests that histone methylation contributes to autoimmunity. Methods. Blood CD4+ T lymphocytes from 26 LADA patients and 26 healthy controls were isolated to detect histone H3 lysine 4 and H3 lysine 9 methylation status. Results. Reduced global H3 lysine 9 methylation was observed in LADA patients’ CD4+ T lymphocytes, compared to healthy controls (P < 0.05). H3 lysine 4 methylation was not statistically different. The reduced H3 lysine 9 methylation was associated with GADA titer but not correlated with glycosylated hemoglobin (HbA1c). When the LADA patient group was divided into those with complication and those without, relatively reduced global H3 lysine 9 methylation was observed in LADA patients with complication (P < 0.05). The expression of histone methyltransferase SUV39H2 for H3 lysine 9 methylation was downregulated in LADA patients, and the expression of histone demethylase KDM4C which made H3 lysine 9 demethylation was upregulated. Conclusion. The reduction of histone H3 lysine 9 methylation which may due to the downregulation of methyltransferase SUV39H2 and the upregulation of demethylase KDM4C was found in CD4+ T lymphocytes of LADA patients.